(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
The financial industry plays a critical part in a country’s economic growth. An economy’s lifeblood is banking. For economic progress, a robust and healthy financial sector is essential. Indian the banking sector is now undergoing an IT revolution. The process of implementation. The use of the internet in banking has revolutionized the industry. It has been successful. Both customers and banks profited from it. In India, e-banking has grown in popularity. Several changes have occurred as a result of technological advancements and innovation. The arrival of the card, Immediate Payment Service, Clear The notion of internet banking and mobile banking, as well as the transfer of funds, are the There have been a number of changes in the banking industry. E-banking is a term that encompasses a variety of services. Online shopping, fund transfer, and mobile banking are all included in this phrase etc. The bank hopes to teach the basic notion of IT via E-Banking. Included Services that are based on the Internet. System of conventional banking it is more convenient for consumers to make debit payments.as well as credit several of the factors why e-banking is gaining popularity in India is because People’s use of the internet is becoming more widespread. Because of the many benefits, electronic banking is becoming more popular. It is linked to it. However, it has raised certain concerns and obstacles. In terms of cybercrime, such as data theft, phishing, and credit card fraud, this paper attempts to provide an overview of electronic banking.in India, as well as the many concerns and challenges that the banking sector faces.